Seleção genômica ampla para volume e qualidade da madeira em eucalipto - Rezende, Breno Alvarenga (2015)
This project aimed to access the feasibility of Genome Wide Selection (GWS) on eucalypt breeding. For that, SNP and DArT markers were used for the early selection of a representative population from Fibria S.A. The population was composed from hybrids, derived from the mating of pre-selected E. grandis, E. urophylla, E. globules and E. camaldulensis plants, and also some interspecies hybrids. Matings were carried out randomly between 45 distinct genitors, which generaed 68 hybrid combinations and 611 individuals. Phenotypic data were collected at 24, 36 and 63 months old, for 20 traits related to volume and wood quality. Some traits were measured at two or more ages. Plants were also genotyped using SNP and DArT markers, totalizing 36,812 and 15,752 polymorphic markers, respectively. GWS analysis were carried out using RR-BLUP methodology. Predictive accuracies of 0.7 and higher were found for most characteristics, for both markers. In average, GWS validation accuracies were 46% and 40% inferiors than the predictive ones, for SNPs and DArTs, respectively. Validation accuracies were highly influenced by trait heritability and also marker heritability. SNPs and DArTs were very similar for predictive capacity (accuracy). GWS showed to be efficient for early selection, mainly for traits related to circumference at breast height and plant height, for both markers.